EEG Findings in Infants With Neonatal Abstinence Syndrome Presenting With Clinical Seizures - Murali Reddy Palla; Gulam Khan; Zahra M. Haghighat; Henrietta Bada (Frontiers Media S.A., 2019)
Neonatal abstinence syndrome (NAS) refers to a constellation of signs occurring in newborn infants who were exposed to opioids or opiates in utero. These manifestations include poor feeding, gastrointestinal disorders, abnormal sleep patterns, and neurological signs such as jitteriness, tremors, and seizures (1, 2). Myoclonus, jitteriness, and tremors often may be interpreted as seizures and therefore treated as epileptic seizures.Objective: To determine whether seizure like activity observed in infants with NAS correlate with electroencephalogram (EEG) findings.Design/ Method: We reviewed the standard EEG or video electroencephalogram (VEEG) of infants with NAS who were admitted because of seizure-like clinical activity. The exclusion criteria were major neurological anomalies, hypoxic ischemic encephalopathy, metabolic disorders, or with clinical diagnosis other than NAS.Results: Forty neonates met study criteria; 28 had standard EEG recordings and 18 had VEEG. Mean gestational age was 38.5 weeks. The onset of seizure-like clinical activity was as early as day 1 and as late as day 16 of life. The clinical seizure-like activity described at the referring hospital were jerking, rhythmic movement of the extremities, or tremors. Only three (7.5%) neonates had epileptic seizures. There were increased sharp transients in frontal, central, temporal, and or occipital regions. VEEG showed disturbed non-rapid eye movement (REM) sleep with frequent arousal, jittery movements, or sleep myoclonus.Conclusion: Clinical seizure-like activity correlates poorly with epileptic seizures in infants with NAS. In neonates with NAS, a VEEG would be useful to determine if the clinical seizure-like activity is of epileptic origin or not, prior to initiation of anti-seizure medications.